2009
DOI: 10.1002/lt.21842
|View full text |Cite
|
Sign up to set email alerts
|

Predicting recurrence after liver transplantation in patients with hepatocellular carcinoma exceeding the up-to-seven criteria

Abstract: The up-to-seven (Up-to-7) criteria [with 7 being the sum of the size and number of tumors for any given hepatocellular carcinoma (HCC)] have been recently proposed to identify potential candidates for liver transplantation (LT) among patients exceeding the Milan criteria. The aim of this study was to compare the ability of the available pathologic staging systems (the Milan, University of California San Francisco, and Up-to-7 criteria) to predict recurrence. A study population of 479 HCC transplanted patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 40 publications
7
101
0
Order By: Relevance
“…18 In another study of 497 patients by D'Amico et al in 2009, histologic grade correlated with HCC recurrence. 26 In our study, univariate analysis showed poor differentiation as an independent factor affecting tumor recurrence and survival (P = .005 [highly significant]). It is not feasible to detect the histologic grade preoperatively except by biopsy.…”
Section: Tumor Differentiationmentioning
confidence: 53%
“…18 In another study of 497 patients by D'Amico et al in 2009, histologic grade correlated with HCC recurrence. 26 In our study, univariate analysis showed poor differentiation as an independent factor affecting tumor recurrence and survival (P = .005 [highly significant]). It is not feasible to detect the histologic grade preoperatively except by biopsy.…”
Section: Tumor Differentiationmentioning
confidence: 53%
“…The Milan group recently reviewed the explant pathological data in 1,556 patients (of the Metroticket project) of which 1,112 were found to have HCC beyond Milan criteria. Despite this, in 283 patients who had the sum of largest tumor diameter in centimeters and number of tumors ≤7 (up to 7 criteria), a 5-year survival of 71% was achieved [17,33]. Faced with low rates of deceased donor liver transplantation (DDLT) and prolonged waiting periods, LDLT is often the only realistic option for patients with HCC in some parts of the world.…”
Section: Extended Criteriamentioning
confidence: 99%
“…The fundamental questions to be answered are what constitutes an acceptable outcome and how much does extension of criteria impact the non-HCC waiting list. A Markov [35] No gross vascular invasion 1-year DFS 83.7% Lesion <8 cm OR 1-year OS 92.8% Lesion ≥8 cm if AFP ≤400 and well-differentiated 5-year DFS 62.4% 5-year OS 70.7% Padua, Italy [33] Sum of number of lesions and diameter ≤7 cm 1-year recurrence 4% 5-year recurrence 14% mathematical model revealed that unless a 5-year survival of at least 61% could be achieved, performing LT for patients with tumors beyond Milan criteria put other patients without HCC at a risk of dying without LT [37]. This survival rate may increase to 71% in regions with severe organ shortage and reduce to 25% in regions where the shortage is not so acute.…”
Section: How Far Is Too Far?mentioning
confidence: 99%
“…16 The prognosis for patients with HCC with highly unfavorable factors (eg, macroscopic vascular invasion) is very poor, so these patients are poor candidates for either DDLT or LDLT outside clinical trials. 11,17,18 Are there reasons to be cautious about preferentially or only offering LDLT for HCC? Yes, there are.…”
Section: Quality Of the Evidence (Cebm Level 2b)mentioning
confidence: 99%